2005
DOI: 10.1002/rra.854
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blockage factors in modelling the resistance of channels containing submerged macrophytes

Abstract: The proportion of a river channel containing vegetation (termed the blockage factor) has historically been determined in three ways: cross-sectional, surface area and volumetric. The first two versions are two-dimensional measures. Meanwhile, the threedimensional volumetric version is biased towards deeper sections of a reach. A fourth version of the blockage factor is proposed that does not have such limitations: the multi-cross-sectional blockage factor. Between five and nine cross-sections were sampled to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 21 publications
4
70
1
2
Order By: Relevance
“…It acts as an additional source of channel resistance and has been shown to alter bulk flow velocities and conveyance [2][3][4], generate turbulence through coherent flow structures [5][6][7][8], modify sediment transport processes [9][10][11] and increase habitat diversity [12,13]. Therefore, a good process understanding of boundary layer flow through and around vegetation is central in predicting the functioning of the fluvial system.…”
Section: Introductionmentioning
confidence: 99%
“…It acts as an additional source of channel resistance and has been shown to alter bulk flow velocities and conveyance [2][3][4], generate turbulence through coherent flow structures [5][6][7][8], modify sediment transport processes [9][10][11] and increase habitat diversity [12,13]. Therefore, a good process understanding of boundary layer flow through and around vegetation is central in predicting the functioning of the fluvial system.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation resistance can be quantified via empirical relationships or with Environ Fluid Mech hydrodynamic models. In the empirical approach, the overall resistance in a vegetated reach is determined via the relationship between biomass and resistance, [17,18] or between blockage factors and resistance [19]. However, it has been demonstrated that hydraulic resistance is also influenced by discharge; and several authors have investigated n-UR relationships [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the characteristic plant area over height needs to be correctly estimated to account for the impact of the vertical vegetation structure on the flow resistance for different stages of submersion [10]. To diminish calibration, recent studies on modeling vegetated flows have focused on physically-based parameterization of woody [7,9,11,12] and aquatic [13][14][15][16] vegetation. The area occupied by vegetation plays a key role in the estimates, and various area-based parameterizations are presented for different types of vegetation: the leaf area index (LAI) [9,17,18], the total area of the trees (Atot) [11], the cross-sectional blockage factor [13,15], and the frontal area per unit volume (AC/V) [19].…”
Section: Introductionmentioning
confidence: 99%